The wall and talus at Barāqish, ancient Yathill (al-Jawf, Yemen): a Minaean stratigraphy - Fedele, Francesco G. (Proceedings of the Seminar for Arabian Studies, 2011)
In 2005-2006 a stratigraphie excavation was carried out by the Italian Archaeological Mission across the outer tell and talus at Baräqish, ancient Yathill, outside the monumental enclosure wall of Minaean age. A sedimentary and cultural sequence spanning a long interval from the Sabaean (late ninth century BC) to the Islamic period was examined. This article focuses on the Minaean segment in order to provide information on its archaeology, activity indicators, sediment accumulation, and radiocarbon dating. The Minaean sequence was investigated by a 52 m-long radial trench through the tell and talus, and a test pit in the adjacent plain to the north-west. A deep sounding down the wall was also taken. This latter revealed the base and foundations of the wall, cut into Sabaean deposits, and a locally complete stratigraphy for the Minaean period characterized by secular — as opposed to cultic — debris and marked environmental interaction (sixth century BC to c. AD 1). Stratified pottery and animal bones were retrieved. This is the first such occurrence in al-Jawf. Construction details of the Yathill wall and its reinforcement bank or 'counter-fort' are discussed, as well as stratified structures, small finds, and camel and donkey dung layers over the talus, which jointly suggest specialization in trading and caravan activities. Together with the Italian work in the temple precinct (A. de Maigret, 1989-2006) such evidence allows inferences for a broader understanding of the Minaean period at Yathill and in its region.